Regional abdominal adiposity is associated with BMI‐related brain regions in middle‐aged adults at high risk of Alzheimer's dementia. (31st December 2021) - Golan, Sapir; Boccara, Ethel; Ravona‐Springer, Ramit; Inbar, Yael; Yore, Iscka; Heymann, Anthony; Beeri, Michal Schnaider
Abstract: Background: There is evidence for the involvement of midlife obesity in mild cognitive impairment (MCI), dementia, and Alzheimer's dementia (AD) risk in late life. Obesity is primarily measured by body mass index (BMI), which poorly reflects body fat distribution. Regional abdominal adiposity has been related to inflammation and metabolic syndrome, both consistently linked to the neuropathology of AD and related disorders (ADRD). We examined the relationship between regional abdominal adiposity and regional brain volume, among middle‐aged adults enriched for AD risk due to parental history of AD. Method: Participants were from the Israel Registry for Alzheimer's Prevention (IRAP), which follows middle‐aged offspring of AD patients (N=390). At this time, 44 participants (Table 1) were scanned, via magnetic resonance imaging (MRI), for regional abdominal adiposity, including hepatic, pancreatic, and abdominal adipose tissues (AAT, visceral (VAT), and subcutaneous (SAT)). T1‐weighted volumetric brain MRI focused on three regions implicated in obesity and cognitive impairment: para‐hippocampus, amygdala, and inferior frontal gyrus (IFG). Following logarithmic normalization, linear regression was used to examine the association of regional abdominal fat with brain volume adjusting for age, sex, education, and intracranial volume. An additional adjustment for BMI was done to examine whether the associations are above and beyond global adiposity. Result: Smaller amygdalar volume was associated with the percentage of VAT fat (r=‐0.324, p=0.044) and approached significance for pancreatic (r=‐0.283, p=0.08) and hepatic (r=‐0.307, p=0.057) fat. A smaller para‐hippocampal volume was associated with the percentage of pancreatic fat (r=‐0.317, p=0.05) and hepatic (r=‐0.447, p=0.004) fat, and approached significance for VAT fat (r=‐0.309, p=0.056). Fat percentage was not associated with IFG volume (Table 2; Figure 1). Conclusion: Greater regional abdominal adiposity was associated with higher amygdalar and para‐hippocampal volumes, already in midlife, regardless of global body adiposity measured by BMI. Regional adiposity affects secreted factors relevant to brain function, suggesting an underlying mechanism. By AAIC 2021, we anticipate 100 IRAP participants will be assessed for regional abdominal adiposity, blood‐based related secreted factors, and brain MRI. These data may lead to the development of age‐specific interventions targeting specific adipose depots, which are expected to prevent or delay neuropathology, cognitive decline, and ultimately AD.